2016
DOI: 10.5944/openpraxis.8.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of MOOC learners’ demographics and motivation: The case of students involved in groups

Abstract: This paper reports preliminary findings on students enrolled in a massive open online course, who were also assigned to work in groups. Part of a larger study on the effect of groups on retention and completion in MOOCs, the paper provides students' demographics (i.e., location, gender, education level, and employment status), and motivation for taking the course. Findings show that women outnumbered men and that students mostly enrolled into the course because of a friend. Indeed, research on MOOCs demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 27 publications
9
48
0
Order By: Relevance
“…In addition, women's persistence and performance in online learning is lower than men (Kizilcec & Halawa, 2015). However, Bayeck (2016) found that the percentage of female was greater than the percentage of male students in her study on group work in MOOCs. This shows the inconsistent findings of past research and indicates that more investigation on the effects on gender on MOOCs adoption is required.…”
Section: Gendermentioning
confidence: 93%
“…In addition, women's persistence and performance in online learning is lower than men (Kizilcec & Halawa, 2015). However, Bayeck (2016) found that the percentage of female was greater than the percentage of male students in her study on group work in MOOCs. This shows the inconsistent findings of past research and indicates that more investigation on the effects on gender on MOOCs adoption is required.…”
Section: Gendermentioning
confidence: 93%
“…They can be used on their own, embedded within a different programme of study or as part of a blended learning strategy (Bruff et al, 2013), offering a broad range of support possibilities for academic institutions. As was the case in this study, MOOCs can benefit different audiences, such as undergraduate students and full-time employees (Bayeck, 2016;Padilla Rodriguez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…MOOCs have been widely used to test different approaches to learning and teaching (Sharples et al, 2014). They can benefit people with different demographic profiles (eg, location, gender, educational level and employment status) and motivations (Bayeck, 2016;Padilla Rodriguez, Estrada Rocha & Rodriguez Nieto, 2017). They seem to have the potential to enhance learner self-efficacy through a well-designed (though often ignored) use of videos, quizzes and discussion forums (Hodges, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some general research into MOOC demographics has been conducted; surveys indicate that these learners are slightly more likely to be male, often have bachelor's degrees, and typically have some level of employment (Bayeck, 2016). Learners in these online courses report a variety of motivations for taking the courses, suggesting at least some lifestyle diversity.…”
Section: Discussionmentioning
confidence: 99%